Truncated Euler-Maruyama Method for Time-Changed Stochastic Differential Equations with Super-Linear State Variables and Hölder’s Continuous Time Variables (Journal of Computational Mathematics, 2025)
An explicit numerical method is developed for a class of non-autonomous time-changedstochastic differential equations, whose coefficients obey Hölder’s continuity in terms of thetime variables and are allowed to grow super-linearly in terms of the state variables. Thestrong convergence of the method in the finite time interval is proved and the convergencerate is obtained. Numerical simulations are provided.